Comparative study of vitamin D3 levels in polycystic ovarian syndrome vs non-polycystic ovarian females - Sachdeva, Manvi; Goel, Kashika; Rai, Meenu; Kukreja, Srishti (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Polycystic ovary syndrome (PCOS) is the most common endocrine disorder in women of reproductive age and has a strong genetic component with a prevalence of 6–10% in the general population. Metabolic disturbances are common in women suffering from PCOS: 30–40% have impaired glucose tolerance and IR with compensatory hyperinsulinemia, and as many as 10% will have type 2 diabetes mellitus by their fourth decade. Recently, vitamin D deficiency has been proposed as the possible missing link between IR and PCOS. Polycystic ovarian syndrome (PCOS) and hypovitaminosis D are the two most common endocrine disorders in young women leading to many adverse metabolic consequences. This study aims to estimate vitamin D3 levels in patients of polycystic ovarian disease and compare it with non PCOS females and to study correlation between Vitamin D3 levels and polycystic ovarian syndrome. Methods: The present patient population case control study was carried out in Department of Obstetrics and Gynaecology of Jaipur Golden Hospital diagnosed involving cases of PCOS and controls of non PCOS (48 each) by random sampling method from September 2019 to June 2021. History, general examination, systemic examination and Vitamin D levels was taken for each patient. Results: Mean vitamin D value of cases was 14.57±6.86 ng/ml and that in controls was 29.31±6.53 ng/ml. When we compared the mean vitamin D value of both the groups, there was statistically significant difference found between the two groups. . We found significant negative correlation found between vitamin D value with age and BMI. Conclusions: Hypovitaminosis D is very common in PCOS patients and exacerbates the metabolic abnormalities. It is essential to screen all the PCOS patients for 25OHD deficiency and institute appropriate replacement therapy to prevent the adverse consequences.